Kidney function, bone-mineral metabolism markers, and calcification of coronary arteries, aorta, and cardiac valves in older adults. (March 2023) - Mok, Yejin; Wang, Frances; Ballew, Shoshana H.; Menez, Steve; Butler, Kenneth R.; Wagenknecht, Lynne; Sedaghat, Sanaz; Lutsey, Pamela L.; Coresh, Josef; Blaha, Michael J.; Matsushita, Kunihiro
Abstract: Background and aims: The contribution of kidney dysfunction, especially at mild-to-moderate stages, and bone-mineral metabolism (BMM) markers to vascular calcification remains controversial or unclear. We comprehensively evaluated the association of kidney and BMM markers with coronary artery calcification (CAC) and extra-coronary calcification (ECC). Methods: In 1931 ARIC participants (age 73–95 years) without coronary heart disease at visit 7 (2018–19), we investigated the associations of estimated glomerular filtration rate (eGFR) (with creatinine, cystatin C, and both) and five serum BMM markers (calcium, fibroblast growth factor 23, magnesium, parathyroid hormone, and phosphorus) with high CAC and ECC (sex-race specific ≥75th vs. <75th percentile Agatston score) or any vs. zero CAC and ECC using multivariable logistic regression. For eGFR and BMM markers, we took their weighted cumulative averages from visit 1 (1987–89) to visit 5 (2011–13). Results: Lower eGFR, regardless of equations used, was not robustly associated with high CAC or ECC. Among BMM markers, only higher phosphorus levels, even within the normal range, showed robust associations with high CAC (only when modeled continuously) and ECC, independently of kidney function (e.g., odds ratio 1.94 [95%CI 1.38–2.73] for high aortic valve calcification, in the highest vs. lowest quartile). Results were generally consistent when analyzing any CAC or ECC, although cystatin C-based eGFR <60 mL/min/1.73 m 2 became significantly associated with mitral valve calcification (odds ratio 1.69 [1.10–2.60]). Conclusions: Among kidney and BMM measures tested, only serum phosphorus demonstrated robust associations with both CAC and ECC, supporting a key role of phosphorus in the pathophysiology of vascular calcification. Highlights: We tested 8 kidney and bone-mineral measures and vascular calcification. Of those measures, phosphorus showed the most robust association. The association was generally continuous and independent of kidney function. The other measures showed no or weak associations.